Safety and Therapeutic Effect of Willfort™ Drops in an Adenine Induced Model of Anemia (Advancements in Homeopathic Research, 2024)
Anemia is a common hematological disorder globally,  often managed with conventional iron supplements  that may lead to gastrointestinal side effects and  poor compliance. Homeopathy, offering a holistic  approach, aims to support the body’s innate healing  mechanism and address the underlying causes of  anemia. This study investigates the safety and efficacy  of homeopathic formulation Willfort™ Anemia  Drops in mitigating adenine-induced Anemia in male  Sprague Dawley rats, revealing encouraging results.  Before this investigation, multiple formulations were  developed in accordance with the internal product  development protocol. Based on expert reviews,  laboratory compatibility trials, and stability studies,  two variants (AD-002/A-20-5 and AD-003/A-20-6)  were selected for this study.
Keywords: outperformed; compliance; Anemia